2001
DOI: 10.1034/j.1600-0625.2001.010002110.x
|View full text |Cite
|
Sign up to set email alerts
|

Doxepin affects acetylcholine induced cutaneous reactions in atopic eczema

Abstract: The clinical and experimental effectiveness of doxepin as an antipruritic drug has been known for years. However, studies focusing on ACH as a pruritogenic mediator have not been performed. The duration of the doxepin application in our study seems to be appropriate since flare and wheal development were diminished. The reason why doxepin did not develop more antipruritic action compared to the vehicle cream may be due to the fact that the doxepin free cream already possessed an antipruritic action in this exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…According to our data, we claim that the antipruritic effect of analgesic drugs might have been less likely arised from the phenomena of allokinesis or hyperkinesis because of the evaluating the acute situations. It is well known that both allokinesis and hyperkinesis are the phenomena seen in the chronic processes, such as atopic dermatitis (Heyer et al 1995, Groene et al 2001. For instance in the study performed by Groene and others (2001), intradermally injected of acetylcholine, which normally provokes pain, provokes itch in patients with atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, we claim that the antipruritic effect of analgesic drugs might have been less likely arised from the phenomena of allokinesis or hyperkinesis because of the evaluating the acute situations. It is well known that both allokinesis and hyperkinesis are the phenomena seen in the chronic processes, such as atopic dermatitis (Heyer et al 1995, Groene et al 2001. For instance in the study performed by Groene and others (2001), intradermally injected of acetylcholine, which normally provokes pain, provokes itch in patients with atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that doxepin didn't have a greater antipruritic effect when compared with placebo, and the author referred it should be due to the moisturizing effect of the base solution used as a placebo, although the dimension of the papule was lower in the forearm that received doxepin, suggesting that acetylcholine caused less reaction. 22 …”
Section: Resultsmentioning
confidence: 99%
“…Nebenwirkungen wurden insbesondere bei mit Doxepin-Creme behandelten Patienten angegeben, die bei 17 Patienten zum Abbruch der Therapie führten. Die starken antipruriginösen Effekte der topischen Doxepin-Behandlung konnten in einer kleineren doppelblinden Studie an 11 Patienten mit atopischer Dermatitis nicht bestätigt werden, bei der der antipruritische Effekt nach Aectylcholin-Injektion der der Basistherapie entsprach [8].…”
Section: » Aufgrund Der Starkenunclassified